Monitoring the organizational wellness of a physician residency program: A quality improvement process. (September 2019) - Talen, Mary R; Edberg, Deb; Pence, Ari; Khan, Laura
Background: Burnout and depression throughout physicians' career cycles have been increasing. There has been a call for medical education leaders to devote resources to bolster the next generation of providers and shift the culture of medicine to organizational initiatives that impact physician well-being. Objective: The goal of this project has been to monitor and improve the organizational wellness of a residency program based on four core organizational areas: (1) culture of meaning and mission, (2) work capacity, (3) control and flexibility in decision-making, and (4) creativity in work–life balance. Method: A quality improvement strategy was implemented to monitor organizational wellness. The wellness was assessed five times over the course of 18 months. The survey was designed to evaluate the four core components. At each time interval, improvement strategies were implemented to address the wellness drains and strengthen drivers. Results: The four time series evaluations (residents: n = 19) indicated that culture of meaning, teamwork, and personal creativity are consistent wellness drivers. Work capacity and lack of control over decision-making were consistent drains. From first until last measurement, there was a slight improvement in control-decision-making; however, the burden of electronic medical record (EMR) charting and strains of coverage continue to drain our residency. Discussion and Conclusions: This model incorporates four categories for assessing organizational wellness within a residency program. The conceptual model is used as a framework to define, measure, analyze, and improve on organizational wellness. This process provides programs with a feedback approach to continually monitor and reassess the wellness of the organizational systems.